When opportunity knocks: how the individual opportunity nexus explains evaluations of new business models. (22nd September 2021) - Klusmann, Christian D.; Spieth, Patrick; Klein, Sascha
The business model concept represents an important assisting mechanism in the venture creation process. However, in the light of opportunity evaluation - a fundamental concept in entrepreneurship literature - the role of the business model lacks clarity. Therefore, we synergise insights from entrepreneurship and business model research. In contrast to previous research that emphasised the antecedents of entrepreneurial intentions, we propose and test quantitatively a causal model with an experimental research design, concerning the link between an individual's general entrepreneurial intention and the evaluation of opportunities. Additionally, we investigate the moderating influence of cognitive decision-making patterns, allowing to contribute to the understanding of cognitive biases in the venture creation. Finally, our empirical investigation offers contributions to both entrepreneurship and business model research by highlighting the role of the business model as an opportunity evaluation concept that accounts for intentional and cognitive differences of individual entrepreneurs and non-entrepreneurs.